2008
DOI: 10.1007/s00128-008-9459-9
|View full text |Cite
|
Sign up to set email alerts
|

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population

Abstract: Humans are exposed to various environmental chemicals such as organochlorine pesticide residues, heavy metals, polychlorinatedbiphenyls (PCBs) etc. There is paucity of data regarding the present blood levels of organochlorine residues in North Indian population with reference to reproductive health. The present study was designed to analyze the levels of organochlorine pesticide residues in maternal and cord blood samples of normal healthy women with full term pregnancy to gain insight into the current status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 11 publications
2
34
1
4
Order By: Relevance
“…Because of its threats to human health and the environment, a global ban on the manufacture and use of endosulfan was negotiated under the Stockholm Convention on persistent organic pollutants in April 2011. However, endosulfan continues to be widely used, particularly in India, the world's largest user and producer of this insecticide (Pathak et al, 2008); however, India has agreed to phase out the use of endosulfan by 2017. In 2009, the production and agricultural use of γ-HCH (lindane) was banned under the Stockholm Convention; it is still used only in some developing countries.…”
Section: Substances Chemical Analysis and Statisticsmentioning
confidence: 99%
“…Because of its threats to human health and the environment, a global ban on the manufacture and use of endosulfan was negotiated under the Stockholm Convention on persistent organic pollutants in April 2011. However, endosulfan continues to be widely used, particularly in India, the world's largest user and producer of this insecticide (Pathak et al, 2008); however, India has agreed to phase out the use of endosulfan by 2017. In 2009, the production and agricultural use of γ-HCH (lindane) was banned under the Stockholm Convention; it is still used only in some developing countries.…”
Section: Substances Chemical Analysis and Statisticsmentioning
confidence: 99%
“…66 Pathak et al 67 first reported endosulfan levels in North Indian population. This study was designed to analyze the levels of organochlorine pesticide residues in maternal and cord blood samples of normal healthy women with full term pregnancy to gain insight into the current status of pesticide burden in newborns.…”
Section: Human Exposurementioning
confidence: 99%
“…It was observed that several EDCs are able to pass through the placenta to the fetus. Many recent studies were devoted to the transmittance of EDC and assessing their content in the cord blood serum and maternal adipose tissue [13][14][15][16][17][18][19][20][21][22][23][24][25][26], showing that a fetus and once born an infant may be exposed to significantly high levels of EDC [27]. This can result in a decrease in fetal birth weight, premature birth, psychomotor retardation and altered cognitive function [28][29][30][31][32][33].…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%